Hubungan Antara Manajemen Waktu Dengan Hasil Belajar Fiqih (Studi Kasus pada Siswa Kelas XI MAN 21 Jakarta) (SAP (Susunan Artikel Pendidikan), 2024)
The relationship between time management practices and academic results in the field of Fiqh (Islamic Law) for grade 11 students at MAN 21 Jakarta. This research, which specifically focuses on the subject of Fiqh, aims to understand how effective time management can improve academic performance. Data was collected from Class XI students using a case study methodology to investigate their time management habits and corresponding academic success in Fiqh. This research adds to our understanding of the factors that influence academic success in Islamic studies, especially in the educational context at MAN 21 Jakarta. This study adopted a quantitative approach and used correlational methods. Likert scales for time management and multiple choice tests for learning outcomes are among the research instruments. This research was sparked by the phenomenon of modern youth preferring to engage in online games on their devices rather than focus on their studies, resulting in a decline in academic performance. Student time management is crucial and has a significant impact on their learning outcomes. Prioritizing essential activities becomes difficult if a student's time management is ineffective, resulting in decreased academic performance. The aim of this research is to determine the relationship between time management and learning outcomes in Islamic Law (Fiqh) among grade 11 students at MAN 21 Jakarta.